Pengaruh Kualitas Pelayanan, Promosi Dan Lokasi Terhadap Kepuasan Konsumen Dengan Perceived Value Sebagai Variabel Mediasi Pada Sektor Pariwisata (Studi Pada Desa Wisata Alam Taman Dolan Kota Batu) - Yussy Nelda Putri Suwandan; Alfian Budi Primanto; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract The tourism sector is vital for regional economic growth, requiring destination management to focus on value creation and consumer satisfaction. This study analyzes the impact of service quality, promotion, and location on consumer satisfaction, using perceived value as a mediating variable at Taman Dolan Nature Tourism Village, Batu City. Grounded in Resource-Based View (RBV) theory, the research treats these factors as strategic resources. Using a quantitative explanatory design, data were gathered from 130 respondents via purposive sampling and analyzed using PLS-SEM with SmartPLS. The results show that service quality significantly affects consumer satisfaction, whereas promotion and location do not. However, both service quality and promotion significantly influence perceived value. Furthermore, perceived value significantly impacts consumer satisfaction and effectively mediates the relationships between service quality, promotion, and satisfaction. The study concludes that enhancing consumer satisfaction in rural tourism depends on strengthening service quality to build positive perceived value for tourists.. Keywords: Service Quality, Promotion, Location, Perceived Value, Consumer Satisfaction